PET amyloid imaging: state of the art and technical considerations - Arminio, Antonietta; Prioreschi, Tommaso (Journal of Biomedical Practitioners, 2022)
INTRODUCTION The development of PET radiopharmaceuticals suitable for the identification and in vivo quantification of β Amyloid plaques has been the focus of intense research, representing a useful means for the non-invasive detection of β Amyloid plaques in subjects affected by the Alzheimer's disease (AD). The purpose of this article is to provide a general overview of the application of PET radiopharmaceuticals currently available for in vivo imaging of β amyloid plaques. The aim is therefore to describe the chemical and synthetic characteristics of the main radiopharmaceuticals currently used in in vivo amyloid imaging and to provide a technical description of the acquisition protocols, always keeping the patient at the center of each step. MATERIALS AND METHODS Radiopharmaceuticals for PET imaging of amyloid β include two broad classes: planar hetero aromatic compounds and alkenes analogs. Among the former are 11C PiB and 18F Flutemetmol. While among the analogues of alkenes, the most used are the following two radiolabelled compounds: [18F] Florbetaben; [18F] AV-45, Florpyramine, [18F] Florbetapir. A suitable and standardized protocol depending on the radiopharmaceutical used together with technical precautions and good communication with the client, contribute to the good quality of the service offered, both in terms of efficacy and safety of the treatments. It is important to have a professional attitude aimed at active listening, to formulate short, precise sentences, composed of simple and clear words, to speak slowly and to give time to respond. The patient with demented syndrome needs a relaxed and non-judgmental environment. Current PET / CT on the market are equipped with tools such as automatic exposure control and iterative algorithms, useful for reducing and optimizing the radiation exposure, the scan parameters may vary depending on the type of scanner. In clinical practice it is commonly used to use 120 KV and 60-100 mA, to obtain a suitable attenuation map and morphological localization. The PET scan is reconstructed using a 256 × 256 matrix using an iterative algorithm with a Gaussian low-pass filter. Both PET and CT data are constructed with a 25-30cm FOV. CONCLUSIONS The radiopharmaceuticals currently available must be known for their respective specifications by the technologist, in order to guarantee the correct acquisition and compliance with the exam timing. An adequate implementation of technical skills and soft communication skills makes an appropriate context for the delicate balance of AD patients, having the patients and their specific needs at the center of health care.